Hepatic Syndecan‐1 Changes Associate With Dyslipidemia After Renal Transplantation. Issue 10 (25th August 2014) - Adepu, S.; Katta, K.; Tietge, U. J. F.; Kwakernaak, A. J.; Dam, W.; van Goor, H.; Dullaart, R. P. F.; Navis, G. J.; Bakker, S. J. L.; van den Born, J.
<x xml:space="preserve">Abstract</x> Syndecan‐1 is a transmembrane heparan sulfate (HS) proteoglycan present on hepatocytes and involved in uptake of triglyceride‐rich lipoproteins via its HS polysaccharide side chains. We hypothesized that altered hepatic syndecan‐1 metabolism could be involved in dyslipidemia related to renal transplantation. In a rat renal transplantation model elevated plasma triglycerides were associated with fivefold increased expression of hepatic syndecan‐1 mRNA (p < 0.01), but not protein. Expression of syndecan‐1 sheddases (ADAM17, MMP9) and heparanase was significantly up‐regulated after renal transplantation (all p < 0.05). Profiling of HS side chains revealed loss of hepatic HS upon renal transplantation accompanied by significant decreased functional capacity for VLDL binding (p = 0.02). In a human renal transplantation cohort (n = 510), plasma levels of shed syndecan‐1 were measured. Multivariate analysis showed plasma syndecan‐1 to be independently associated with triglycerides (p < 0.0001) and inversely with HDL cholesterol (p < 0.0001). Last, we show a physical association of syndecan‐1 to HDL from renal transplant recipients (RTRs), but not to HDL from healthy controls. Our data suggest that after renal transplantation loss of hepatic HS together with increased syndecan‐1 shedding hampers lipoprotein binding and uptake by the liver contributing to dyslipidemia. Our data open perspectives toward improvement of lipid profiles by targeted inhibition of syndecan‐1 catabolism in renal transplantation.